Asynchronous Teledermatology Reduces Wait Times and Maintains High Adherence to Standard Care for Lichen Planus: A Retrospective Study - Taylor L. Duffy; Joseph C. English (Telemedicine Reports)
Background: Lichen planus (LP) is a chronic inflammatory dermatosis with limited teledermatology data guiding its management. Objective: To assess whether asynchronous teledermatology provides timely, guideline-adherent LP care comparable to in-person visits. Methods: A retrospective study of 102 LP patients seen via asynchronous teledermatology (n = 45) or in-person (n = 57) from 2020 to 2024. Variables included demographics, response time, diagnostic concordance, treatment, and follow-up compliance. Results: Teledermatology provided rapid access (mean response time: 15 h) to dermatologic care. Diagnostic concordance between teledermatologists and in-person dermatologists was high (90.5%), while concordance with primary care providers was lower (18.5%, p < 0.001). Teledermatologists followed LP care standards, including hepatitis C virus screening (91.1%) and topical corticosteroid initiation (90%). Black patients used eVisits more frequently than in-person care (38.9% vs. 8.8%, p < 0.01), and follow-up compliance was lower among asynchronous patients (57.8% vs. 92.7%, p < 0.001). Conclusion: Asynchronous teledermatology enables timely, high-quality LP care. However, strategies to improve follow-up are needed, particularly for younger teledermatology patients.